2017
DOI: 10.1080/01436597.2017.1333417
|View full text |Cite
|
Sign up to set email alerts
|

Hurdles to peace: a level-of-analysis approach to resolving Sudan’s civil wars

Abstract: Why do some peace agreements end armed conflicts whereas others do not? Previous studies have primarily focused on the relation between warring parties and the provisions included in peace agreements. Prominent mediators, however, have emphasised the importance of stakeholders at various levels for the outcome of peace agreements. To match the experience of these negotiators we apply a level-of-analysis approach to examine the contextual circumstances under which peace agreements are concluded. While prominent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

7
2

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Does MI termination in turn increase the likelihood of intrastate conflict termination, perhaps depending on termination type? The termination of the MIs between Sudan and its neighbors removed a major obstacle to peace between the Sudanese government and the SPLM/A (Brosché and Duursma 2018), which suggests that at least in some instances peace can trickle down from the international to the national level. In short, we hope this note is merely a first step in developing what promises to be an exciting research program on mutual interventions in Africa and beyond.…”
Section: Discussionmentioning
confidence: 99%
“…Does MI termination in turn increase the likelihood of intrastate conflict termination, perhaps depending on termination type? The termination of the MIs between Sudan and its neighbors removed a major obstacle to peace between the Sudanese government and the SPLM/A (Brosché and Duursma 2018), which suggests that at least in some instances peace can trickle down from the international to the national level. In short, we hope this note is merely a first step in developing what promises to be an exciting research program on mutual interventions in Africa and beyond.…”
Section: Discussionmentioning
confidence: 99%
“…First, previous research has found that the conflict in Darfur is difficult to resolve because many different stakeholders operate at different levels, including local, national, regional and international levels. The many interlinkages between these different levels add to the intractable nature of the Darfur conflict (Brosché & Duursma, 2017). One fruitful avenue for future research would be to examine how the connections of local conflict parties influence their propensity to make peace or not (Duursma, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Non-state conflicts are often tied to individuals in the capital or other major urban centers with interests in these conflicts. These actors from urban centers often instrumentalize non-state conflicts in the periphery to further their own interests (Brosché and Duursma 2018; Duursma 2021b; De Waal 2015; Stearns et al 2017). One central challenge to resolving non-state conflicts is therefore ensuring that these external actors do not undermine the peace process.…”
Section: The Argumentmentioning
confidence: 99%